Power BI and SQL Server Dashboard Data for Monitor Transportation Presence Employees at PT PON Gresik - Frayudha, Angga Debby; Agung, Hamzah (Department of Informatics Engineering, 2024)
Employee presence is a crucial aspect in office management. It reflects the way employees work in a company and can impact their productivity. A high level of productivity can indicate achievement of company targets. However, this attendance data is often large and has not been processed. To turn it into valuable information, Business Intelligence (BI) software is needed that is able to visualize employee attendance and transportation data. This research aims to create a dashboard that shows employee attendance data, including entry hours and attendance status, as well as transportation data such as expenditure for each type of vehicle and travel destination code. Microsoft Power BI was used for data visualization, while Microsoft SQL Server Management Studio was used to create the database. Data is collected and processed so that it can become a source of information. The research results include a daily attendance dashboard with peak attendance at 08.00 and 21.00. The trip dashboard shows the highest fare with travel code